RETAINING MILLENNIAL EMPLOYEES IN THE WORKPLACE: A LITERATURE REVIEW - Evelin Hudiono; Reza Lidia Sari (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
Desire to leave organization (turnover intention) is a phenomenon that has increased in recent years, especially for Millennial employees that dominate the job market now and have unique characteristics which require special attention. This systematic literature review aimed to identify the factors that influence turnover intention in Millennial employees. On 25 June 2022, a search on three databases: SAGE Journals, Springer Link, and Web of Science, and keywords â€œturnover intention*â€ AND â€œMillennial*â€ OR â€œgeneration yâ€ OR â€œgen-yâ€, with year filter 2019-2022, showed 73 relevant articles. Furthermore, applying the inclusion and exclusion criterias, there were 5 articles selected. The results showed that the influencing factors are: psychological contract violations, work-life balance, job characteristics (task and knowledge), work fulfillment, and the quality of relationship with colleagues. By knowing these factors, organizations can use them as a reference in formulating strategies to retain Millennial employees in the workplace.